Christianity and Modern Healthcare in Guizhou - TAN, Houfeng (Journal of Research for Christianity in China (JRCC), 2025)
This paper examines the relationship between the medical activities of modern church groups and missionaries in Guizhou, the Christian spirit of charity, missionary work, and social reform. Healing the sick and saving lives was, in essence, merely an emulation of Jesus’ own acts of mercy during his earthly ministry. Yet the medical services provided by missionaries in Guizhou not only attracted many Miao, Yi, and Han people to embrace Christianity, but also objectively alleviated the shortage of medical care and medicines in rural and remote ethnic minority areas. This significantly advanced the dissemination and development of modern Western medical technology in Guizhou, greatly enhanced public health awareness, and promoted the reform of social customs within the province.